Steady state performance of anaerobic degradation of palm oil mill effluent (POME) at various hydraulic retention time (HRT) - Yee, Shian Wong (School of Industrial Technology, Universiti Sains Malaysia, 2014)
The steady state performance of anaerobic stabilization pond treatment of Palm Oil Mill Effluent (POME) was carried out in a laboratory anaerobic bench scale reactor (ABSR). The ABSR was operated by a series of continuous experiments using feed flow-rates of 0.63, 0.76, 0.95, 1.27, 1.9 and 3.8 liters of raw POME per day, which correspond to the hydraulic retention time (HRT) of 60, 50, 40, 30, 20 and 10 days. The steady state performance showed that the treatment of POME could be treated effectively through ABSR at different HRT. The chemical oxygen demand (COD) removal efficiency was in the range of 85.41% and 66.38% between 60 days and 10 days of HRT. Besides, the biomass concentration of ABSR was between 18418 and 28694 mg MLVSS/l. Moreover, the pH level and total alkalinity of the ABSR were reduced from 8.55 until 7.64 and 18320 until 12772 mg CaCO3/l, respectively from the HRT of 60 days until 10 days.